Child maltreatment and aggressive behaviors in early adolescence: evidence of moderation by parent/child relationship quality - Fagan, Abigail A. (Child maltreatment, 2020)
The cycle of violence suggests that maltreatment increases children’s aggression, but research shows that many children are resilient to the harms caused by maltreatment. This study examines whether or not parent/child relationship quality accounts for variation in the impact of maltreatment on aggression and hypothesizes that the effect will be weaker for children who have better relationships with their caregivers. Race differences in these effects are also examined. Based on prospective data from a high-risk sample of 620 (207 White and 413 Black) families in the Longitudinal Studies of Child Abuse and Neglect, ordinary least squares regression analyses indicated that youth with at least one official allegation of maltreatment before age 10 had significantly more frequent aggressive behaviors at age 12. The direct effect of maltreatment on aggression did not vary for Black and White youth. However, a significant three-way interaction indicated that parent/child relationship quality buffered the relationship between maltreatment and aggressive behaviors for White but not Black children. Although additional research is required to identify factors that ameliorate the impact of maltreatment for Black youth, the findings support the need for interventions to help children cope with maltreatment and to strengthen parent/child relationships.